2019
DOI: 10.18297/jri/vol3/iss1/5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Real-time PCR assay for Pneumocystis jirovecii on the Luminex ARIES® Platform

Abstract: Pneumocystis pneumonia (PCP) is an opportunistic infection caused by the fungus Pneumocystis jirovecii. Infection with P. jirovecii can result in serious illness in patients with a weakened immune system, and can lead to death if it is not properly diagnosed and treated. Direct detection of P. jirovecii in lower respiratory tract specimens such as bronchoalveolar lavage (BAL) is preferred for rapid diagnosis, a laboratory service currently not available locally. We report here the development of a diagnostic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…As a result, an E. coliebased Pneumocystis mtSSU run control was generated by transforming mtSSU plasmids into competent E. coli cells, which can go through all the of the Pneumocystis mtSSU ARIES PCR assay. Considering variation in BALF quality and viscosity, as well as the rigid and thick Pneumocystis cell walls rendering DNA extraction difficult, 3,16,28 pretreatment steps, including bead beating and proteinase K digestion, were added to sample processing. BALF specimens were spiked with the Pneumocystis run controls (mtSSU gene containing E. coli) and then tested with and without pretreatment steps.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, an E. coliebased Pneumocystis mtSSU run control was generated by transforming mtSSU plasmids into competent E. coli cells, which can go through all the of the Pneumocystis mtSSU ARIES PCR assay. Considering variation in BALF quality and viscosity, as well as the rigid and thick Pneumocystis cell walls rendering DNA extraction difficult, 3,16,28 pretreatment steps, including bead beating and proteinase K digestion, were added to sample processing. BALF specimens were spiked with the Pneumocystis run controls (mtSSU gene containing E. coli) and then tested with and without pretreatment steps.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that targeting mtSSU rather than mtLSU may increase the sensitivity of detection of P. jirovecii, which has been suggested by other investigators as well. 18,30 Furthermore, the mtSSU target region of the ARIES PCR assay had a higher melting temperature (80.1 C) than mtLSU (78.2 C), 16 which enabled us to set up a higher and wider melting temperature window for mtSSU (78.8 C to 82.5 C), thereby avoiding non-specific amplification and contributing to a higher specificity. 16,31e33 In the clinical evaluation, the mtSSU ARIES PCR assay demonstrated a specificity of 94.6% (139/147) in detecting P. jirovecii, which is close to the top range of specificity (82.7% to 95.5%) reported from numerous validation studies of P. jirovecii nucleic acid amplification tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…250 pM to 1 nM. However, our system is faster, simpler, and requires no especial equipment or trained personnel [ 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%